2018
DOI: 10.1063/1.5026252
|View full text |Cite
|
Sign up to set email alerts
|

Strange nonchaotic and chaotic attractors in a self-excited thermoacoustic oscillator subjected to external periodic forcing

Abstract: We experimentally investigate the synchronization dynamics of a self-excited thermoacoustic system forced beyond its phase-locked state. The system consists of a laminar premixed flame in a tube combustor subjected to periodic acoustic forcing. On increasing the forcing amplitude above that required for phase locking, we find that the system can transition out of phase locking and into chaos, which is consistent with the Afraimovich–Shilnikov theorem for the breakdown of a phase-locked torus. However, we also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…The prototypical thermoacoustic system under study consists of a laminar conical premixed flame in a tube combustor subjected to external acoustic forcing. Figure 1 shows the experimental set-up, which is identical to that of our recent studies on periodic thermoacoustic oscillations (Guan et al 2018(Guan et al , 2019a and which is modelled after the numerical set-up of Kashinath et al (2018). The system has four main components: a stainless steel burner (inner diameter, ID: 16.8 mm; length: 800 mm), a quartz tube combustor with double open ends (ID: 44 mm; length: L = 860 mm), an acoustic decoupler (ID: 180 mm; length: 200 mm) and a loudspeaker for acoustic forcing.…”
Section: Experimental Set-up and Data Analysismentioning
confidence: 88%
See 3 more Smart Citations
“…The prototypical thermoacoustic system under study consists of a laminar conical premixed flame in a tube combustor subjected to external acoustic forcing. Figure 1 shows the experimental set-up, which is identical to that of our recent studies on periodic thermoacoustic oscillations (Guan et al 2018(Guan et al , 2019a and which is modelled after the numerical set-up of Kashinath et al (2018). The system has four main components: a stainless steel burner (inner diameter, ID: 16.8 mm; length: 800 mm), a quartz tube combustor with double open ends (ID: 44 mm; length: L = 860 mm), an acoustic decoupler (ID: 180 mm; length: 200 mm) and a loudspeaker for acoustic forcing.…”
Section: Experimental Set-up and Data Analysismentioning
confidence: 88%
“…Balusamy et al (2015) applied similar off-resonance forcing to a swirl-stabilized turbulent premixed combustor and found additional synchronization dynamics, such as frequency pushing and pulling as well as phase locking, slipping, drifting and trapping -the latter a partially synchronous feature defined by frequency locking without phase locking (Li & Juniper 2013c). For high forcing amplitudes, Guan et al (2018) found that a synchronized system can transition out of synchronization and into strange non-chaotic and chaotic states, behaving in line with the Afraimovich & Shilnikov (1991) theorem for the collapse of a phase-locked torus.…”
Section: Forced Synchronization Of Periodic Oscillationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Afterwards, several numerical studies have demonstrated the existence of SNAs in systems such as pendulum [5], Duffing oscillator [6], logistic map [7], Henon map [8], and circular map [9].The experimental discovery of SNA was reported by Ditto et al[10] in a quasiperiodically forced system with a buckled magnetoelastic ribbon. In subsequent years, there have been several experimental observations of SNAs in practical systems [11][12][13][14][15]; however, all these studies presented the necessity of having quasiperiodic forcing to generate SNAs. Contrary to these studies, Negi et al [16] showed theoretically that the need of quasiperiodic forcing is not mandatory for the creation of SNAs, and it could happen in naturally driven systems as well without the need of external forcing.…”
mentioning
confidence: 99%